The Effect of Ultisols Subsoil Combined with Mexican Sunflower (Tithonia diversifolia) Compost and Vermicompost on Pre-Nursery Growth of Oil Palm Seedling - Hutabarat, Grace May Sawita; Simanihuruk, Bilman Wilman; Herison, Catur; Muktamar, Zainal; Hairani, Putri Mian; Suprijono, Eko (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2023)
The productivity of oil palm is determined by the use of high-quality seedlings that have good growth potential, appearance, and the ability to grow in various environmental conditions. To obtain good oil palm seedlings, attention must be paid to the planting media used. The objective of this research was to determine the appropriate composition of planting media, consisting of Ultisols subsoil, compost, and vermicompost, for oil palm seedlings in the pre-nursery stage. This study was conducted from January to April 2023, used a Completely Randomized Design (CRD) with a single factor consisting of 10 treatments, which are 100% Ultisols subsoil, 80% Ultisols subsoil + 20% mexican sunflower compost, 80% Ultisols subsoil + 20% vermicompost, 60% Ultisols subsoil + 20% mexican sunflower compost + 20% vermicompost, 60% Ultisols subsoil + 10% mexican sunflower compost + 30% vermicompost, 60% Ultisols subsoil + 30% mexican sunflower compost + 10% vermicompost, 60% Ultisols subsoil + 40% mexican sunflower compost 60% Ultisols subsoil + 40% vermicompost, 50% Ultisols subsoil + 50% mexican sunflower compost, 50% Ultisols subsoil + 50% vermicompost. The research results showed that the composition of 60% Ultisols subsoil + 40% vermicompost provided the best growth for oil palm seedlings in the pre-nursery stage, as evidenced by seedling growth parameters such as plant height, number of leaves, leaf area, root volume, root dry weight, crown dry weight, and plant dry weight Keyword: mexican sunflower compost, pre nursery, ultisols subosil, vermicompost.